2019
DOI: 10.1089/cbr.2019.2846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EGFR-TK Expression with a 99mTc-Labeled Complex Bearing Quinazoline Pharmacophore

Abstract: Objectives: The epidermal growth factor receptor (EGFR) signaling pathway is widely recognized to play an important role in development and progression of many malignant tumors, including lung cancer. The aim of this study was to produce a useful technetium-99m (99m Tc) complex for early detection and staging of EGFRpositive tumors. Methods: The authors labeled quinazoline derivative (3-iodinephenyl) quinazoline-4, 6-diamine with 99m Tc using S-acetylmercaptoacetyltriglyglycinate (MAG 3) conjugated to quinazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It can be due to the high affinity and rapid clearance from blood and nontarget tissues of 99m Tc-MPHH, which increases the contrast images by reducing the background (Table , Figure ). …”
Section: Discussionmentioning
confidence: 99%
“…It can be due to the high affinity and rapid clearance from blood and nontarget tissues of 99m Tc-MPHH, which increases the contrast images by reducing the background (Table , Figure ). …”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the reported 99m Tc-labeled quinazoline derivatives [ 10 , 11 , 12 , 13 ], the 4-anilinoquinazoline pharmacophore was coupled to tailor-made chelators suitable for the stabilization of either the M III (M = Re and 99m Tc) core with a ‘‘4+1′’ mixed-ligand system or the tricarbonyl fac -[M I (CO) 3 ] + core. It was shown that the presence of the organometallic core does not deteriorate the pharmacological properties of the 4-anilinoquinazoline pharmacophore.…”
Section: Introductionmentioning
confidence: 99%